Job Burnout and Performance of Staff Nurses in Selected Hospitals in Metro Manila (Global Journal of Medical Research, 2020)
This study was conducted to determine the job burnout and performance of staff nurses in selected tertiary hospitals in Manila using the Oldenburg Burnout Inventory. Results showed that there's: a high degree of agreement in relation to burnout of the staff-nurses in terms of exhaustion and disengagement; an average level of performance of the staff nurses in terms of task performance, contextual performance and counter-productive behavior; significant differences between the degrees of agreement in relation to job burnout of the staff-nurses (disengagement and exhaustion) when they are grouped according to nurse-patient ratio and census per area, and no significant differences for the rest of the profile variables except when group according to age in terms of exhaustion; a significant difference between the levels of performance of the staff nurses when grouped according to length of work experience as nurse practitioner as to task performance, contextual performance and overall performance; when they are grouped according to nurse-patient ratio as to task performance; when they are grouped according to census per area as task performance and counterproductive work behavior; significant relationships between the degree of agreement in relation to job burnout (disengagement) and overall level of performance of the staff nurses.
Keywords: job burnout; performance of staff nurses; job burnout and performance of staff nurses